2014
DOI: 10.3389/fneur.2014.00195
|View full text |Cite
|
Sign up to set email alerts
|

Chiari 1 Malformation Presenting as Central Sleep Apnea during Pregnancy: A Case Report, Treatment Considerations, and Review of the Literature

Abstract: Purpose: Chiari malformation (CM) type-1 frequently causes obstructive or central sleep-disordered breathing (SDB) in both adults and children, although SDB is relatively rare as a presenting manifestation in the absence of other neurological symptoms. The definitive treatment of symptomatic CM is surgical decompression. We report a case that is, to our knowledge, a novel manifestation of central sleep apnea (CSA) due to CM type-1 with severe exacerbation and initial clinical presentation during pregnancy.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…9,34 Although a large percentage of patients with CM-I are asymptomatic, a sudden unexpected deterioration and/or death has been reported in CM-I, most often after surgery, infection, or other significant stressors such as pregnancy. 30,32,35 The pathology of CM-I leading to tonsillar herniation, CMI-associated syringomyelia, and subsequent symptoms is not completely understood. However, studies have suggested that a combination of both extradural and intradural pathology contributes to its pathogenesis, often showing signs of posterior fossa crowding, brainstem compression, an enlarged fourth ventricle, or mechanical obstructions of CSF outflow.…”
Section: Observationsmentioning
confidence: 99%
“…9,34 Although a large percentage of patients with CM-I are asymptomatic, a sudden unexpected deterioration and/or death has been reported in CM-I, most often after surgery, infection, or other significant stressors such as pregnancy. 30,32,35 The pathology of CM-I leading to tonsillar herniation, CMI-associated syringomyelia, and subsequent symptoms is not completely understood. However, studies have suggested that a combination of both extradural and intradural pathology contributes to its pathogenesis, often showing signs of posterior fossa crowding, brainstem compression, an enlarged fourth ventricle, or mechanical obstructions of CSF outflow.…”
Section: Observationsmentioning
confidence: 99%
“…Both epidural and spinal anesthesia case studies have been reported in literature [7,9,21]. Nonetheless, regional anesthesia techniques also must be preceded with a caution, as an accidental dural puncture may have severe consequences [5]. Dural punctures lead to unavoidable loss of CSF which may cause tonsillar herniation through the foramen magnum and further leads to an increase in intracranial pressure [7,9].…”
Section: Modes Of Anesthesiamentioning
confidence: 99%
“…CM-I affects people of all races, although with an increased prevalence in women than men. The symptom complex of CM-I is very broad range which could include post-tussive suboccipital headaches, vertigo, dizziness, vertebrobasilar insufficiency, blurring of vision, nystagmus, tinnitus, poor coordination, numbness & tingling, swallowing difficulty, central sleep apnea, tremors, nausea, and/or mental fog [2,5,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment during pregnancy is with an adaptive servoventilaton device, and postpartum such patients might need surgical decompression of the base of the skull. 15…”
Section: Treatment Of Osa In Pregnancymentioning
confidence: 99%